PENGARUH PEMBERIAN KOMPRES HANGAT TERHADAP PENURUNAN INTENSITAS DISMENOREA PADA SISWI KELAS VIII - Murtiningrum, Fajar Heni; Rahmawati, Anita; Maryani, Tri (Poltekkes Kemenkes Yogyakarta, 2015)
Adolescence is characterized by biological changes in menstruation periods in which women feel discomfort or pain in the lower in abdomen. This called menstrual pain. Giving warm compress will be dilates blood vessels and increase local blood flow which resulting relaxation and can reduce pain. The purpose of research was to determine the impact warm compress towards the decreasing of dysmenorrhea intensity. The design of this pre-experimental (one group pre-posttest design). The sites were on SMP Negeri 3 Depok, Sleman. The population was students who have experience dysmenorrhea that met inclusion area. In the beginning, students filled out the menarche, duration, and menstrual cycles. Students were given explanation about warm compress procedure. Before and after do the warm compress, do the measurement of pain intensity first. All procedure is done by the respondents. The data were analyzed using statistic test with significance level = 0,05. The result showed before given warm compress the range of pain intensity about 3 up to 5with the highest intensity on scale 4 (46,7%)with mean 3,8. And after given warm compress had decrease pain's scale about 2 up to 4 with the highest intensity on scale 3 with mean 2,83, mean difference of 0,967 (Cl 95%, lower 0,847. Upper 1,086) value 0,0001 < 0,05 so the warm compress can reduce the menstrual pain. The conclusion is warm compress can reduce the dysmenorrhea intensity.